Urban agriculture: transforming of innovation among farmers' in Malaysia - Zainal, Milah; Hamzah, Siti Raba'ah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Following the phenomenal increase in the cost of living in the city, the government is committed to guarantee the quality and food security of the population in the country. Accordingly, as a strategy for increasing food productivity there are a variety of methods, technologies and innovations that have been introduced. Urban agriculture is a practical approach among the urban population to produce their own food defined as all activities done related to agriculture and agricultural activities in the urban area. It can reduce daily expenses due to the rise in cost of living in the city. However, the acceptance of urban agriculture among farmers in the city was influence by their cognitive, affective and behavioral. Thus, present study aims to study the current stance of the process of acceptance and practice of urban agriculture among urban farmers, for being successful in the future urban agriculture activities.